Improving the quality of the performance and delivery of continuous renal replacement therapy (CRRT) to critically ill patients across a healthcare system: QUALITY CRRT: a study protocol. Issue 2 (4th February 2022) - Opgenorth, Dawn; Reil, Ellen; Lau, Vincent; Fraser, Nancy; Zuege, Danny; Wang, Xiaoming; Bagshaw, Sean M; Rewa, Oleksa
Abstract : Introduction: Continuous renal replacement therapy (CRRT) is a continuous form of dialysis used to support critically ill patients with acute kidney injury. The ideal delivery of CRRT requires ongoing monitoring and reporting to adjust practice and deliver optimal therapy. However, this practice occurs variably. Methods: QUALITY CRRT is a multicentre, prospective, stepped-wedged, interrupted time series (ITS) evaluation of the effectiveness, safety and cost of implementing a multifaceted CRRT quality assurance and improvement programme across an entire healthcare system. This study will focus on the standardisation of CRRT programmes with similar structure, process and outcome metrics by the reporting of CRRT key performance indicators (KPIs). The primary outcome will be the quarterly performance of CRRT KPIs. Secondary outcomes will include patient-centred outcomes and economic outcomes. Analysis will compare pre-implementation and post-implementation groups as well as for the performance of KPIs using an ITS methodology. The health economic evaluation will include a within-study analysis and a longer-term model-based analysis. Discussion: The effective delivery of CRRT to critically ill patients ideally requires a standardised approach of best practice assessment and ongoing audit and feedback of standardised performance measures. QUALITY CRRT will test the application of this strategy stakeholder engagement and stepped-wedged implementation across an entire healthcare system. Ethics and dissemination: This study has received ethics approval. We will plan to publish the results in a peer-reviewed journal. Trial registration number: NCT04221932 . Protocol version: 1.0 (15 June 2020).